Special pre-stress extrusion screw rod for granulating solid waste - YANG SONG (2017)
The invention relates to the technical field of solid waste management and in particular relates to a special pre-stress extrusion screw rod for granulating solid waste. The special pre-stress extrusion screw rod is characterized by comprising a tip cone nut, a tip cone nut sleeve, a core shaft I, a core shaft II, a spiral reamer ring assembly and a key. The tip cone nut is used for applying pre-stress to the spiral reamer ring assembly; in a working process, the stress is transmitted to the core shafts through the tip cone nut; the core shafts are not subjected to stress or bear relatively small stress after two-phase equilibrium, so that the core shafts have long service life. 本发明涉及固体废弃物治理技术领域，具体涉及种利用固体废弃物造粒专用预应力挤出螺杆。其特征是：包括顶锥螺母、顶锥螺母套座、芯轴Ⅰ、芯轴Ⅱ、螺旋铰刀环组件、键。由顶锥螺母向螺旋铰刀环组件施加预应力，工作时应力经顶锥螺母传导到芯轴时由于两相平衡后不受力或承载较小的应力，那么就能让芯轴有长期的寿命。